Electromagnetic Wave Scattering on Nonspherical Particles Basic Methodology and Simulations - Rother, Tom.; Kahnert, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book gives a detailed overview of the theory of electromagnetic wave scattering on single, homogeneous, but nonspherical particles. Beside the systematically developed Green$1 (Bs function formalism of the first edition this second and enlarged edition contains additional material regarding group theoretical considerations for nonspherical particles with boundary symmetries, an iterative T-matrix scheme for approximate solutions, and two additional but basic applications. Moreover, to demonstrate the advantages of the group theoretical approach and the iterative solution technique, the restriction to axisymmetric scatterers of the first edition was abandoned.s
Scattering as a Boundary Value Problem -- Filling the Mathematical Tool Box -- First Approach to the Green Functions: The Rayleigh Method -- Second Approach to the Green Functions: The Self-Consistent Way -- Other Solution Methods -- The Rayleigh Hypothesis -- Physical Basics of Electromagnetic Wave Scattering -- Scattering on Particles with Discrete Symmetries -- Numerical Simulations of Scattering Experiments -- Recommended Literature.
Keywords: Physics; Microwaves; Physics; Optics and Electrodynamics; Atomic, Molecular, Optical and Plasma Physics; Astrophysics and Astroparticles; Microwaves, RF and Optical Engineering; Numerical and Computational Physics